A Facile and Efficient One-pot Three Component Route to New Bis(1,2,4- Oxadiazole) Linked with Polyoxyethylene Chain - Ghrab, Saad; Aroua, Lotfi; Beji, Mohamed (Letters in Organic Chemistry, 2017)
Background: The synthesis of effective drugs is very important for the scientist. Due to the beneficial pharmacological properties of certain molecules containing the 1,2,4-oxadiazole moiety, the aim of this manuscript is to develop a one pot three component reaction for the synthesis of bis (3, 5- disubstituted 1,2,4-oxadiazoles) bridged by polyoxyethylene chain from bis(β-hydroxynitrile) of polyethylene glycols under neutral and organic solvent-free reaction conditions. These compounds have gained too much interest as proven by large number of reviews and research articles published in the current years. The synthesis of a series of bis (3, 5-disubstituted 1,2,4-oxadiazoles) has initially been stimulated by their known antimalaria properties. Methods: A one-pot two-step synthesis of a new bis (3, 5-disubstituted 1,2,4-oxadiazoles) linked with polyoxyethylene chain was realized starting from the reaction of aqueous hydroxylamine with bis (β- hydroxynitrile) polyoxyethylene obtained in turn by ring opening of oligoethylene diglycidyl ethers under mild conditions. The identity and purity of the products were confirmed by IR, 1H NMR, 13C NMR and HRMS. Results: The synthesized compounds with different chain lengths were obtained in satisfactory to good yields (41-74%).This methodology presented the advantage of being relatively eco-friendly, short reaction times, versatile and avoid the use of organic solvent. Conclusion: This work presents simple direct route to the important structure containing two oxadiazole groups bridged by a polyoxyethylene chain 3(a-d), which would facilitate relevant studies on the pharmacological properties of these oxadiazole derivatives.
Keywords: hydroxynitrile